New approaches to creating ultralight solar arrays for ultrasmall spacecrafts - Borshchov, V.M.; Listratenko, O.M.; Protsenko, M.A.; Tymchuk, I.T.; Kravchenko, O.V.; Bilousov, K.G.; Perekopskyi, I.T. (Radiotekhnika, 2025)
New approaches to selecting design-technological solutions of improved relatively flexible ul-tralight solar modules based on aluminium-polyimide boards using the most novel thin multi-junction GaAs solar cells of a new generation with an efficiency of 30% – 32% were developed in this work. The developed approaches confirm principal possibility of manufacturing ultralight solar modules with an area of about 250 cm2 with specific power per area about 336 – 364 W/m2 and significantly increased specific power per mass not less than 309 – 453 W/kg (for solar cells 30% and 32% efficiency respectively) at BOL for solar arrays of ultra-small CubeSat-class spacecrafts, as well as for solar modules for solar arrays of stratospheric drone (quasi-satellites). The technology proposed by the authors’ team is used for manufacturing reliably protected solar arrays on carbon-plastic ultralight panels and relatively flexible aluminium-polyimide solar modules based on thin 3G30C – Advanced solar cells 80 microns thick with efficiency 30% from AZUR SPACE Solar Power company for CubeSat – 3U class spacecrafts. The developed new approaches allow manufacturing solar arrays with their total thickness up to 840 microns and mass no more than 42 g, what is 2,5 times less than for domestic ultra-small CubeSat – 3U spacecraft "GS-1" type from Yuzhnoye design office. At the same time, the estimated specific energy efficiency of such solar arrays at BOL for AM0 conditions, T = 25ºС over the area can be about 336 W/m2. The estimated specific energy efficiency of the arrays by mass can be at least 200 W/kg with a specific mass of the solar arrays by area about 1,55 kg/m2.